FREQUENCY OF POLYCYTHEMIA IN PATIENTS PRESENTING WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (The Research of Medical Science Review, 2025)
BACKGROUND:Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition characterized by chronic airflow limitation and hypoxia. Polycythemia, defined as an abnormal increase in red blood cell mass, can occur in response to chronic hypoxemia in COPD patients. This adaptive response may improve oxygen delivery but also increases blood viscosity, predisposing patients to thromboembolic complications. Despite its clinical importance, local data on the prevalence of polycythemia among COPD patients is limited.OBJECTIVE:To determine the frequency of polycythemia in patients presenting with chronic obstructive pulmonary disease.METHODS:A cross-sectional study was conducted in the Pulmonology Department of Lady Reading Hospital, Peshawar, over a period of six months following approval from CPSP. A total of 100 COPD patients aged 30–70 years were enrolled using consecutive non-probability sampling. Patients with hematological disorders, autoimmune diseases, or renal failure were excluded. Data on demographic and clinical variables were collected using a structured proforma. Polycythemia was assessed based on operational definitions. Data were analyzed using IBM SPSS version 25. Descriptive statistics, chi-square test, and Fisher’s exact test were applied, with p ≤ 0.05 considered significant.RESULTS:Out of 100 patients, polycythemia was identified in 12% of cases. The condition was significantly associated with factors such as age group, BMI, residence, socioeconomic status, education level, smoking, diabetes, and hypertension (p < 0.05). The majority of polycythemic patients were males, urban residents, overweight or obese, and had coexisting chronic conditions.CONCLUSION:Polycythemia was observed in a notable proportion of COPD patients, highlighting the importance of routine screening in this population. Early detection and management are essential to reduce the risk of complications such as thrombosis. These findings support the need for integrated care strategies targeting high-risk COPD patients to improve outcomes and quality of life